The role of tumor-associated macrophages in oral squamous cell carcinoma - Xue, Yiwen; Song, Xiao; Fan, Siyu; Deng, Runzhi (Frontiers in Physiology, 2022)
Oral squamous cell carcinoma (OSCC) is a common head and neck cancer with a high recurrence rate and a low five-year survival rate. Tumor associated macrophages (TAMs) is an important immune-inflammatory cell in tumor microenvironment, which plays an important role in the progression of many tumors and is related to the poor prognosis of tumors. This article reviews the origin of TAMs, the role of TAMs in the invasion, metastasis, angiogenesis and immunosuppression of OSCC, and points out the therapeutic strategies targeting TAMs, hoping to provide new ideas for the treatment of oral squamous cell carcinoma.